Applying autocad 2004 - Wohlers, Terry T. (McGraw - Hill, 2005)
Applying AutoCAD 2004 is a comprehensive, basic CAD textbook providing step-by-step instruction for new users of the AutoCAD computer-aided drafting and design software, version 2004. It covers the AutoCAD commands and functions used to create, edit, store, and print engineering drawings.